2021
DOI: 10.1177/09603271211035674
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of pyrrolidine dithiocarbamate against methotrexate-induced testicular damage

Abstract: The aim of the study was to investigate the protective effect of pyrrolidine dithiocarbamate (PDTC) against methotrexate (MTX)-induced testicular damage in rats. Forty Wistar albino male rats were divided into equally four groups: Control group (saline solution, IP), PDTC group (100 mg/kg PDTC,IP, 10 days), MTX group (20 mg/kg MTX, IP, single dose, on the 6th day) and MTX + PDTC group (100 mg/kg PDTC, IP, 10 days and 20 mg/kg MTX, IP, single dose, on the 6th day). After 10 days, testicular tissues were excised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
(135 reference statements)
1
6
0
Order By: Relevance
“…Anywise, it was twigged that co-administration of pyrrolidine dithiocarbamate along with tramadol significantly elevated these hormonal parameters in the tramadoltreated group. Similar results have been declared by Delen et al (2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Anywise, it was twigged that co-administration of pyrrolidine dithiocarbamate along with tramadol significantly elevated these hormonal parameters in the tramadoltreated group. Similar results have been declared by Delen et al (2021).…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, according to previous literature search, PDTC treatment significantly improved serum FSH, LH, and testosterone hormone levels and had antioxidant and anti-inflammatory with a protective impact on testicular tissue by decreasing prokineticins and NFkB expressions and elevating expressions of Nrf2. So, it was thought that PDTC can participate in the management of methotrexate-induced testicular injury and infertility (Delen and Uz 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It inhibits oxidative stress, decreases lipid peroxidation, and exerts neuroprotection via the activation of NRF2 signaling pathway in astrocytes. Delen and co-workers [ 37 ] reported that in addition to reducing the expressions of NF-ĸB and Prokineticin 2 (PK2) levels, pyrrolidine dithiocarbamate ( I ) exerts a protective effect against methotrexate-induced testicular damage via upregulating the expression level of NRF2. Contrarily, it has been reported that while pyrrolidine dithiocarbamate deactivates NF-ĸB and upregulates some antioxidant enzymes, its administration has no effect on NRF2/KEAP pathway in dextran sodium sulfate (DSS)-induced colitis [ 38 ].…”
Section: Nitrogen Heterocycles As Modulators Of the Nrf2 Pathwaymentioning
confidence: 99%
“…Even though this mechanism may contribute to the mechanism by which MTX suppresses in ammation, other mechanisms of action including increased adenosine release, inhibition of transmethylation reactions essential for some cellular functions, decreased polyamine accumulation and NO synthase uncoupling have been proposed (3). Despite its bene cial effects, MTX has several major side effects and can cause toxicities in organs such as the liver, kidneys, testes and brain (4)(5)(6)(7). Protecting the organs from undesired side effects could be one way to mitigate the negative consequences of MTX in therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%